Serum biomarkers of cardiovascular complications in COVID-19 - R. M. Gumerov; D. F. Gareeva; P. A. Davtyan; R. F. Rakhimova; T. I. Musin; Sh. Z. Zagidullin; A. E. Pushkareva; M. R. Plotnikova; V. Sh. Ishmetov; V. N. Pavlov; L. J. Motloch; N. Sh. Zagidullin (Российский кардиологический журнал)
The coronavirus disease 2019 (COVID-19) affects not only the respiratory system, but also the cardiovascular system in 20-28% of cases, causing endothelial dysfunction, vasculitis, hyper- and hypocoagulation, myocarditis, endothelial dysfunction and other adverse effects. The presence of cardiovascular risk factors and diseases has been shown to worsen the disease severity and increase mortality from COVID-19. Recent studies have also found that elevations in some serum cardiovascular biomarkers can stratify the disease severity, in particular rates of hospitalizations to an internal medicine or intensive care unit, intubation, and mortality. They can be divided into markers of damage (TnT/I, creatine phosphokinase (CPK) and CPK-MB, myoglobin, NT-proBNP), coagulation (prothrombin time, fibrinogen and D-dimer), as well as prospective biomarkers for which the available evidence base is limited but there is a pathophysiological rationale (homocysteine and sST2). This review presents studies on the use of above serum biomarkers to stratify the risk of death in patients with COVID-19.